Variabilidad fotosintética en genotipos contrastantes de sorgo bajo estrés salino - Luna, Dario Fernando; Ortiz, Diego; Ferreira, F. Nogueira; Cordeiro, C.J. Xavier; Morais, F.M. da Silva; Pittaro, Gabriela; Bustos, Dolores Angela (INTA y Facultad de Ciencias Agropecuarias, Universidad Nacional de Córdoba, 2025)
Poster y resumen